The organization of treatment of casualties with acute injuries - Berezka, Mykola (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
By means of transformation of the admission department and creation of a specialized department for multiple injuries, a staged and continuous system was developed for giving medical aid to casualties with acute multiple systemic and organic injuries. This system preserves succession in rendering aid and effectively uses the staff, diagnostic and medical potentials of the hospital. The creation of trauma centres in multi-type medical establishments makes it possible to admit all the injured, irrespective of their state, as well as of the localization and combination of their injuries. The territorial and administrative integrity of diagnostic and clinical departments of the hospital makes it possible to avoid any wastes of time and finances.